Association of urinary biomarker COLL2-1NO2 with incident clinical and radiographic knee OA in overweight and obese women. Issue 8 (August 2015) - Landsmeer, M.L.A.; Runhaar, J.; Henrotin, Y.E.; Middelkoop van, M.; Oei, E.H.G.; Vroegindeweij, D.; Reijman, M.; van Osch, G.J.V.M.; Koes, B.W.; Bindels, P.J.E.; Bierma-Zeinstra, S.M.A.
Summary: Objective: To investigate the association between urinary biomarker Coll2-1NO2 (uColl2-1NO2 ) and incident knee OA after 2.5 years follow-up in middle-aged overweight and obese women at high risk for knee osteoarthritis (OA). Design: Data were used from PROOF, a randomized controlled trial with 2.5 years follow-up evaluating the preventive effects of a diet and exercise program and oral glucosamine sulphate (double blind and placebo controlled), on development of incident knee OA in women with body mass index ≥ 27 kg/m 2 without signs of knee OA at baseline. Baseline and 2.5 years uColl2-1NO2 concentrations were assessed with enzyme-linked immunosorbent assay (ELISA). Primary outcome measure was incidence of knee OA in one or both knees, defined as incidence of either Kellgren & Lawrence grade ≥2, joint space narrowing of ≥1.0 mm or knee OA according to the combined clinical and radiographic ACR-criteria. We used binary logistic regression for the association analyses. Results: 254 women were available for analyses. At 2.5 years follow-up, incident knee OA was present in 72 of 254 women (28.3%). An inversed association was found between baseline uColl2-1NO2 and incident knee OA at 2.5 years (OR 0.74, 95% CI 0.55–0.99 ) . The concentration at 2.5 years and the change in concentration over 2.5 years did not show significant associations with the outcome. Conclusions: In overweight and obese middle-aged women, not higher but lower baseline uColl2-1NO2 concentration was significantly associated with an increased risk for incident knee OA. This interesting but counterintuitive outcome makes further validation of this biomarker warranted.